2019
DOI: 10.1071/en18279
|View full text |Cite
|
Sign up to set email alerts
|

Impact of (nano)formulations on the distribution and wash-off of copper pesticides and fertilisers applied on citrus leaves

Abstract: Environmental contextThere are great concerns around current wide usage of copper-based agrochemicals. We compare the fate of nano- and conventional forms of copper, in particular their resistance to wash-off by rain (rainfastness), following their application to citrus leaves. Results showing large differences between the formulations in the amount and forms of copper washed from the leaves provide essential information to optimise agrochemical efficacy while minimising the environmental impact. AbstractThis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 47 publications
4
36
0
Order By: Relevance
“…Previous size fractionation studies of Cu from Kocide in water found that 100% of Cu species were below 0.45 μm, with 20% passing through a 0.1 μm filter. 29 Kocide also contains 1−5% of (undefined) clays, 5−10% 2-propenoic acid, and 38.9− 47.9% of "other proprietary ingredients". 28 These organic phases may influence ENM fate once released in the environment.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Previous size fractionation studies of Cu from Kocide in water found that 100% of Cu species were below 0.45 μm, with 20% passing through a 0.1 μm filter. 29 Kocide also contains 1−5% of (undefined) clays, 5−10% 2-propenoic acid, and 38.9− 47.9% of "other proprietary ingredients". 28 These organic phases may influence ENM fate once released in the environment.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Simulated wash of LSP particles on leaves. The release of Cu upon wetting of LSP previously dried on the leaves was evaluated following the protocol described by Kah et al 38 with minor modications. Newly emerged citrus leaves were collected, gently washed with DI water, and air dried.…”
Section: Characterization Of Lsp Particlesmentioning
confidence: 99%
“…In a previous study, 29 we considered a series of nine wellcharacterised formulations of Cu, including nano and conventional Cu-based formulations, as well as their salt or bulk equivalents. A wash off study carried out on citrus leaves highlighted a wide range of behaviour in terms of rainfastness among the nine formulations (i.e.…”
Section: Introductionmentioning
confidence: 99%